Alarmin IL-33 elicits potent TB-specific cell-mediated responses - Villarreal, Daniel O (Hum Vaccin Immunother, 2015)
Tuberculosis (TB) still remains a major public health issue despite the current available vaccine for TB, Bacille Calmette Guerin (BCG). An effective vaccine against TB remains a top priority in the fight against this pandemic bacterial infection. Adequate protection against TB is associated with the development of T(H)1-type and CD8(+) T cell responses. One alarmin cytokine, interleukin 33 (IL-33), has now been implicated in the development of both CD4(+) T(H)1 and CD8(+) T cell immunity. In this study, we determined whether the administration of IL-33 as an adjuvant, encoded in a DNA plasmid, could enhance the immunogenicity of a TB DNA vaccine. We report that the co-immunization of IL-33 with a DNA vaccine expressing the Mycobacterium Tuberculosis (Mtb) antigen 85B (Ag85B) induced robust Ag85B-specific IFNγ responses by ELISpot compared to Ag85B alone. Furthermore, these enhanced responses were characterized by higher frequencies of Ag85B-specific, multifunctional CD4(+) and CD8(+) T cells. Vaccination with IL-33 also increased the ability of the Ag85B-specific CD8(+) T cells to undergo degranulation and to secrete IFNγ and TNFα cytokines. These finding highlights IL-33 as a promising adjuvant to significantly improve the immunogenicity of TB DNA vaccines and support further study of this effective vaccine strategy against TB.